The long-term prognosis of nephropathy in operated reflux. Issue 6 (December 2019) - Matsuoka, Hirofumi; Tanaka, Masatoshi; Yamaguchi, Takanori; Miyazato, Minoru; Kihara, Toshiharu; Nakagawa, Masayuki; Mori, Ken-ichi; Kamimura, Toshio
Summary: Objective: To investigate the postoperative long-term prognosis and the factors predicting the renal function of patients with reflux nephropathy. As the serum creatinine (s-Cr) level tends to increase during infancy, the degree of reflux and renal parenchymal damage are thought to be more important factors in pediatric patients than in older patients. Materials and methods: This study examined s-Cr, urinary protein, and blood pressure of patients who underwent anti-reflux surgery 10 years before. It also calculated the postoperative estimated glomerular filtration rate (eGFR) and examined the correlation between the eGFR and preoperative factors (age, gender, number of urinary tract infections [UTIs], primary diagnosis, reflux grade, percentage of dimercaptosuccinic acid uptake, degree of renal parenchymal damage, s-Cr abnormality, proteinuria, and hypertension), and analyzed the factors associated with the long-term prognosis. Results: The study population was 51 infants (37 boys and 14 girls). The mean age of the patients before surgery and at the follow-up examination was 3.41 ± 3.61 and 14.63 ± 3.74 years, respectively. After surgery, the s-Cr, urinary protein, and blood pressure values showed (44.7%, 26.7%, and 18.2%, respectively) were abnormal. The postoperative eGFR was a mean 90.27 ± 20.42 ml/min/1.73 m 2 and primary correlated with an older age ( P = 0.0361), no UTI at the primary diagnosis ( P = 0.0044), reflux grade ≥8 ( P = 0.0180), degree of renal parenchymal damage (group ≥2b, P < 0.0001), s-Cr abnormality ( P < 0.0001), and proteinuria ( P = 0.0001) at baseline. A total of 20 patients had chronic kidney disease (CKD; Fig. 1). The multiple regression analysis of these factors revealed that an older age ( P = 0.0021), reflux grade ≥8 ( P = 0.0134), and degree of renal parenchymal damage (group ≥2b, P < 0.0001) were significantly associated with the long-term postoperative prognosis of reflux nephropathy. Using these three factors, this study derived a multiple regression equation estimating eGFR in the 10th year after surgery (Fig. 1). Discussion: In this study, severe vesico-ureteral reflux (reflux grade ≥8) and severe renal parenchymal damage (group ≥2b) were associated with a long-term decrease in the eGFR. In particular, renal parenchymal damage was closely correlated with the postoperative eGFR; thus, this was clearly a critical factor. The age at surgery showed a better correlation with the postoperative eGFR in the multiple regression analysis; thus, age was regarded as an independent prognostic factor. Conclusions: The age, reflux grade, and degree of renal parenchymal damage at baseline were factors that affected the long-term postoperative prognosis of reflux nephropathy. Patients with high-grade reflux and severe renal parenchymal damage were more likely to show a reduced CKD level at 10 years after anti-reflux surgery.